Faktor yang Mempengaruhi Mutu Pelayanan Keperawatan terhadap Tingkat Kepuasan Pasien di Rawat Inap Penyakit Dalam RSUD Pirngadi Kota Medan - Azmiatussahliah Azmiatussahliah; Tri Niswati Utami; Arifah Devi Fitriani (Jurnal Kesehatan Amanah, 2025)
Nursing services are an important component in the hospital system and are one of the main indicators of the quality of health services. This study aims to analyze the influence of the quality of nursing services on the satisfaction of inpatients at Dr. Pirngadi Hospital, Medan City. The research design used an analytical approach with a cross sectional design, involving 97 inpatient respondents in the internal medicine section selected through purposive sampling techniques. The research instrument is in the form of a structured questionnaire that measures five dimensions of service quality based on the SERVQUAL model (tangible, reliability, responsiveness, assurance, empathy). Data analysis used multivariate logistic regression to identify the dominant factors influencing patient satisfaction. The results showed that all dimensions of nursing service quality were significantly related to patient satisfaction (p < 0.05). The most dominant factor is assurance with an Odds Ratio (OR) value of 23,292, which shows that service assurance, sense of security, and competence of health workers are the main determinants of patient satisfaction. This study emphasizes that improving the quality of nursing services as a whole, especially in the aspects of assurance and empathy, is an important strategy in increasing patient satisfaction and hospital competitiveness.